Modelling the Growth of Salmonella spp. and Escherichia Coli O157 on Lettuce. (2016) - Veys, Olivier; Elias, Susana de Oliveira; Sampers, Imca; Tondo, Eduardo César
Abstract: This study aimed to model the growth of Salmonella and Escherichia coli O157 on lettuce at different temperatures. Microorganisms were inoculated separately on lettuce and stored at 5, 10, 25, and 37°C. Growth curves were built by fitting the data to the Baranyi's DMFit model and Ratkowsky equation was used as secondary model. The models were able to assess the growth of both microorganisms and data showed that bacteria did not growth for 24hours at 10°C, what can be a suitable temperature for lettuce distribution on food services. However, prolonged periods demonstrated growth at every temperatures examined.